SYSTEM OF CONTROL OF KNOWLEDGE, SKILLS OF STUDENTS IN STUDYING THE DISCIPLINE "ECONOMICS" - O.O. Pavlenko (Academy of Cognitive and Natural Sciences, 2022)
In the article the problem of the control of knowledge, abilities, of trainees is considered. Own the variant of the monitoring system of knowledge, abilities of pupils on a subject «Economy» is offered (S. V. Stepanenko s curriculum). The periodic (thematic) control of knowledge, abilities of pupils to the fourth section «National economy» is developed (the program S.V. Stepanenko's «Economy»).